IMPLEMENTASI AL-QUR’AN DAN HADIST DALAM PRAKTIK DAKWAH: TELADAN NABI MUHAMMAD SAW - Nurani, Dewi; Muhibuddin, Muhibuddin; Wulansari, Intan; Nazih, Abdullah Ghulam; Triskova, Ellya (Spektra: Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to analyze the implementation of the Qur'an and Hadith in the practice of da'wah and examine the example of the Prophet Muhammad SAW which can be used as a guideline for da'i and da'wah practitioners today. The focus of this study is to analyze how the values ​​of Islamic teachings are applied concretely in various forms of da'wah interactions, both in the personal and social realms, which include the relationship between da'i and mad'u, da'wah communication patterns, strategies for conveying religious messages, and the community's response to da'wah in the context of everyday life. The application of these values ​​is not only understood as the delivery of normative teachings, but also as an effort to ground Islamic principles such as noble morals, justice, tolerance, and wisdom in diverse social realities. This study uses a descriptive qualitative approach with a literature study method, through data collection from the Qur'an, Hadith, tafsir books, da'wah literature, and related scientific journals. The analysis is carried out using content analysis techniques to interpret the relevant Qur'anic and Hadith arguments, and compare them with the da'wah practices of the Prophet Muhammad SAW. The results of the study show that da'wah based on the Qur'an and Hadith emphasizes the principles of patience, gentleness, honesty and wisdom, which are reflected in the Prophet's various strategies such as a personal approach, delivering da'wah in stages, and emulating noble morals.